2021
DOI: 10.1051/e3sconf/202131701069
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Environmental Education to Achieve Sustainable Development: Literature Review

Abstract: Environmental issues arise in different regions due to human activities using the natural resources without considering the sustainability for future generations. Education has an important role in the sustainable development because it is related to other sustainable development goals. The purpose of this study is to analyze the implementation of environmental education through Education for Sustainable Development (ESD) approach. A literature review of previous research studies used to identify the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Analyzed the implementation of environmental education through ESD approaches [14]. The study found that environmental education and ESD share similar approaches, such as interdisciplinary, lifelong learning, and prioritizing local culture in solving local and international problems.…”
Section: Environmentalmentioning
confidence: 99%
“…Analyzed the implementation of environmental education through ESD approaches [14]. The study found that environmental education and ESD share similar approaches, such as interdisciplinary, lifelong learning, and prioritizing local culture in solving local and international problems.…”
Section: Environmentalmentioning
confidence: 99%
“…The current education system must produce students who are environmentally literate in order to have sufficient knowledge about environmental issues and a caring attitude to behave responsibly (Liang et al, 2018;Maulaa et al, 2020;Solheri et al, 2022). The purpose of integrating EE into the curriculum structure is to build awareness, increase knowledge, shape attitudes, increase participation, and evaluate the surrounding environment (Abdullah et al, 2018;Mashaba et al, 2022;Permanasari et al, 2021;Zsóka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%